Non-Hierarchical Associative Relationships: Their Types and Computer-Generation of RT Links - Neelameghan, A.; Ravichandra Rao, I. K. (Journal of Information and Knowledge, 1976)
Two approaches to semi-mechanical method of generating a thesaurus based on a scheme for classification and faceted subject structuring respectively, are mentioned. The problems in identifying non-hierarchical associative relationships (NHR) among ideas are indicated. About thirty types of NHR, taken from different sources are enumerated. The representation of NHRs between component ideas of subjects as facet relation (FR), spectator relation (SpR), Coordinate relation (CR) and Phase relation (PR) according to S R Ranganathan’s model for structuring of subject is illustrated with examples. The use of the subject structures as data base for computer-generation of thesaurus and guidelines for direct representation of the NHR—identified as FR, SpR, CR and PR—as RT links in the thesaurus are briefly discussed. COBOL programs for generating a thesaurus from subject headings of a bibliographical record are discussed.